Optimal linear redistributive tax and pension systems with flexible labor supply - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
The tax system redistributes labor incomes among workers, the pension system redistributes incomes from workers to pensioners. We consider a linear transfer system, where workers pay pension contributions and personal income taxes and pensioners receive proportional benefits, while workers and pensioners enjoy basic income. Every worker maximizes his discounted lifetime utility function, depending on young- and old-age consumption plus leisure. The government chooses a transfer system which maximizes the undiscounted social welfare function. Our major result is as follows: The optimal transfer system balances the efficiency of proportional pensions and the guarantee of the basic income.
Keywords: H24; I31; J22; J26; 330; personal income tax; pension system; optimal redistribution; Steuersystem; Einkommensteuer; Gesetzliche Rentenversicherung; Verteilungsgerechtigkeit